Dioxin- and POP-Contaminated Sites-Contemporary and Future Relevance and Challenges - Weber, Roland; Gaus, Caroline; Tysklind, Mats; Johnston, Paul; ter, Martin; Hollert, Henner; Heinisch, Emanuel (Environmental science and pollution research international, 2008)
The challenges regarding dioxin and persistent organic pollutants (POP) contamination for reducing pollution, were evaluated. Policies related with the identification and remediation of contaminated sites varied considerably among different countries. An evaluation production practices could be used to analyze the potential contamination associated with the production of elemental chlorine in the chlor-alkali process. Most of the solid residues of chemical industries were/are typically discharged to landfills and dumps. The production, use and disposal of chemicals and approaches to the remediation in industrialized countries could be used to minimize the recurrence of contamination. Public awareness also facilitated better management of new chemicals that spread contamination.